2020
DOI: 10.1016/j.drugalcdep.2020.108191
|View full text |Cite
|
Sign up to set email alerts
|

State medical marijuana laws, cannabis use and cannabis use disorder among adults with elevated psychological distress

Abstract: Background.-Cannabis use and cannabis use disorder are more prevalent in U.S. states with medical marijuana laws (MMLs), as well as among individuals with elevated psychological distress. We investigated whether adults with moderate and serious psychological distress experienced greater levels of cannabis use and/or disorder in states with MMLs compared to states without MMLs.Methods.-National Survey of Drug Use and Health data (2013)(2014)(2015)(2016)(2017) were used to compare past-month cannabis use, daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
3
0
2
Order By: Relevance
“…McBain and colleagues found that rates of cannabis use and CUD are higher for individuals reporting moderate or severe psychological distress as reported in the National Survey of Drug Use and Health. However, cannabis use and CUD were no different among individuals with moderate or high psychological distress in states with legal medical cannabis compared to states without 59 …”
Section: Public Health Concernsmentioning
confidence: 75%
See 1 more Smart Citation
“…McBain and colleagues found that rates of cannabis use and CUD are higher for individuals reporting moderate or severe psychological distress as reported in the National Survey of Drug Use and Health. However, cannabis use and CUD were no different among individuals with moderate or high psychological distress in states with legal medical cannabis compared to states without 59 …”
Section: Public Health Concernsmentioning
confidence: 75%
“…However, cannabis use and CUD were no different among individuals with moderate or high psychological distress in states with legal medical cannabis compared to states without. 59…”
Section: Cannabis Use Disordermentioning
confidence: 99%
“…(37) In the present study, trends began to diverge in 2015, when only two states had legalized recreational cannabis, but 23 had legalized cannabis for medical use. (38) Prior research has shown higher rates of cannabis use in medical cannabis states and among individuals with SPD but no interaction between medical cannabis laws and SPD, (39) suggesting that the presence of medical cannabis laws alone do not fully explain this relationship. A recent study of recreational cannabis marketing in California found that high density of marketing promoting the health benefits of cannabis was associated with a 2-3x increased odds of cannabis use among adults exposed to health messaging.…”
Section: Discussionmentioning
confidence: 99%
“…No parece haber una asociación entre la ansiedad elevada y los patrones de consumo de cannabis en los estados de EE.UU. con la marihuana legalizada para uso medicinal, siendo el consumo de cannabis más frecuente en estos estados (McBain et al, 2020).…”
Section: Repercusiones De La Legalización Sobre Las Urgencias Psiquiá...unclassified